2016
DOI: 10.1111/ijd.13307
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with facial psoriasis in Malaysia

Abstract: This study found that facial psoriasis is not as rare as previously thought. Ambient ultraviolet light, sebum, and contact with chemicals from facial products may reduce the severity of facial psoriasis, but these factors do not reduce the prevalence of facial psoriasis. The association with younger age, younger age of onset, higher percentage of body surface area involvement, higher DLQI of > 10, nail involvement, and hospitalization due to psoriasis support the notion that facial psoriasis is a marker of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
13
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 15 publications
9
13
1
2
Order By: Relevance
“…Early onset of psoriasis (before 40 years old) is often associated with a more severe course of the condition . Several authors have found a relationship between the early onset of symptoms and the presence of facial involvement on psoriasis . In line with these findings, our study found that 52.4% of patients with lesions on the face had a diagnosis of psoriasis established before the 5th decade of life, while only 34.9% of patients without facial lesions had a diagnosis until this cutoff.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Early onset of psoriasis (before 40 years old) is often associated with a more severe course of the condition . Several authors have found a relationship between the early onset of symptoms and the presence of facial involvement on psoriasis . In line with these findings, our study found that 52.4% of patients with lesions on the face had a diagnosis of psoriasis established before the 5th decade of life, while only 34.9% of patients without facial lesions had a diagnosis until this cutoff.…”
Section: Discussionsupporting
confidence: 89%
“…There was no predominance of gender between the two groups, which was also found in some previous studies . However, two studies observed a 1.6–2.5 times greater prevalence of facial involvement in males …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations